Estudio de factibilidad para la creación de una empresa de servicio de alquiler de equipos para la construcción en la ciudad de Loja. - Esparza Sarmiento, Carlos Rolando (2023)
The general objective of the investigative work is to determine the feasibility of creating a company dedicated to providing construction equipment rental services in the city of Loja. For the development of the specific objectives, various methods were used such as: deductive, inductive, statistical and descriptive, as well as the use of different investigative techniques such as direct observation and surveys, which allowed the collection of information of great importance. importance to analyze various aspects related to supply, demand and marketing plan. As a first step, a market study was carried out, taking as a study population 1850 unionized construction professionals in their specific area; Considering 50 companies that are dedicated to the rental of construction machinery and equipment as an offer. After an extensive analysis through market research, it was concluded that there is a large unsatisfied demand for 44,781 construction equipment rental services per year, a very favorable aspect for entrepreneurship and the start-up of a company, that is dedicated to this type of activity in the city of Loja The macro and micro location of the company was carried out, where aspects such as: availability of labor, main access roads, basic services were analyzed, determined that the location of the company will be in the Loja Canton, Loja province, Ciudad sector. Victoria, a place close to the city center and that has all the requirements for the implementation of the company. In the organizational study, the constitution of the company was determined, which will have the trade name of "Loja construction equipment rental company". The staff that will work in the company is made up of the Manager, a Legal Adviser, Secretary, and two operators, whose activities and obligations are described in the functional, structural, and positional organizational chart of the company, and their responsibilities are structured in a Function's manual. In the economic study, it was analyzed that the total investment will be $163,418.52, which will be financed with 18% of the members' contribution and 82% with a loan to the "CoopMego" Savings and Credit Cooperative with a rate of 11,25% per year. The retail price of the service, as well as the profit margin, will vary depending on the rented property. Subsequently, the break-even point was defined for the first and fifth years of the project's useful life based on the income and the capacity of the company. Its results are shown graphically in the economic study of the project. The financial evaluation of the project was carried out where the VAN $ 1,018,150.37 and the IRR of 75.18% higher than the annual interest rate of the Savings and Credit Cooperative "COOPMEGO" with an annual rate of 11.25%. Keywords: feasibility project, company, market study, financial evaluation